OVERVIEW OF MALARIA PARASITE AND ITS PREVENTION IN INDIA - Raza, Adil; Chaudhary, Megha; Devi, Sonika (Journal of Biomedical and Pharmaceutical Research, 2019)
Background: Malaria is a systematic disease caused by a parasite called Plasmodium which is transmitted into the human blood via female Anopheles mosquito. Malaria in humans is caused by four species of protozoan parasites of the genus Plasmodium: P. falciparum, P. vivax, P. ovale, and P. malariae. The parasite enters the human body through a mosquito bite and travel to the very crucial organ, the liver, where they multiply and come back to the bloodstream and destroy red blood cells. Malaria causes symptoms that typically include fever, tiredness, vomiting, and headaches. In severe cases it can cause yellow skin, seizures, coma, or death. Symptoms usually begin ten to fifteen days after being bitten by an infected mosquito. In those who have recently survived an infection, reinfection usually causes milder symptoms. Objectives: Isolation of different species of malaria parasites. The prevalence of malaria parasite in India. Methods: The procedure follows these steps: collection of peripheral blood, staining of smear with Leishman’s stain and examination of red blood cells for malaria parasites under the microscope. Results: We observed the plasmodium species in peripheral blood smear. Conclusion: Worldwide, the number of cases of malaria caused by Plasmodium falciparum, the most dangerous species of the parasite, is on the rise.